Photon‐Pen Writing for Metal Oxide‐Based Versatile Nanosensors. (12th July 2022) - Bae, Garam; Kim, Minji; Jang, Moonjeong; Kwon, Yeong Min; Yim, Soonmin; Song, Wooseok; Myung, Sung; Lee, Sun Sook; Hasan, Tawfique; An, Ki‐Seok
Abstract: Low‐temperature processes and simplification of lithographic techniques are key challenges for the fabrication of solution‐processed metal oxide‐based nanodevices. Recent breakthroughs in location‐specific synthetic methodologies involving inkjet printing and photon‐activation routes have enabled lithography‐free and bottom‐up fabrication of such devices. However, a revolutionary strategy to resolve room‐temperature direct fabrication of metal oxide‐based materials still remains elusive. Here, a pertinent route enabling wafer‐scale, location‐specific direct‐writing, termed "photon‐pen writing (PPW), " of functional metal oxide‐based devices is proposed. Using PPW, fabrication of elaborate patterns of metal oxides is demonstrated through location‐specific dechlorination and subsequent oxidation via thermal energy transfer of a focused infrared laser in ambient environment. By tailoring process parameters, precise manipulation of the chemical and structural features of the PPW‐produced metal‐oxide patterns are demonstrated. The versatility of the PPW process by realizing a highly sensitive, stable, uniform, and wafer‐scale nanosensor array for gas and light detection using PPW‐ZnO channel and PPW‐ITO electrodes is demonstrated, with 4.1% of response at 50 ppb NO2 and 2.93 ± 0.23 µ A of photocurrent for 0.76 mW cm −2, 254 nm UV light. A new route toward wafer‐scale production of bespoke nanosensor arrays onto single chip for next‐generation nanoelectronics is introduced. Abstract : A pertinent route enabling wafer‐scale, location‐specific direct‐writing, termed "photon‐pen writing (PPW), " for functional metal oxide‐based devices is proposed. Using PPW allows for the fabrication of elaborate patterns of metal oxides through location‐specific dechlorination and subsequent oxidation via thermal energy transfer of a focused infrared laser. Wafer‐scale bespoke nanosensor arrays is demonstrated on a single chip.